Lithographic lecture notes. A tool of forensic medicine teaching. Observation on the lessons of Paolo Pellacani (1884-1885), forensic physician at the University of Pavia - Birkhoff, Jutta Maria; Pezzoni, Barbara; Badino, Paola; Iorio, Silvia; Gorini, Ilaria (Acta Biomedica Atenei Parmensis, 2020)
We focus our attention on the use of lithographed lecture notes written by professors, or more often by students, in the teaching of medicine and surgery courses, between the late 19th and early 20th centuries, a period in which, to better understand the phenomena underlying life and death, collaboration between medical professionals and natural science researchers was intense (1). In particular, we analyzed the lithographed lecture notes of Professor Paolo Pellacani at the University of Pavia for the course of legal medicine.